Practical training report at Cosmopoint Sdn Bhd Sungai Petani, Kedah / Badariah Mohd Isa and Mardiana Mangsor - Mohd Isa, Badariah; Mangsor, Mardiana (Universiti Teknologi MARA, Kedah, 2007)
Practical Training Background The Faculty of Information Technology and Quantitative Science (CS110), Mara University of Technology (UiTM) has made it compulsory for each of their final semester students to carry out with practical training at any organization set by the faculty or by the student's preferences. Each practical trainee will undergo a 4 months or at least 16-weeks of training scheme at their selected organization before going back to nearest UiTM that have CS 110 faculty to present their work.